ANALYSIS OF LIBRARY SERVICE QUALITY IN IMPROVING STUDENT SATISFACTION AT THE STATE UNIVERSITY OF MAKASSAR LIBRARY - Eritrina Eritrina; Anita Reski Amalia (JURNAP: Jurnal Administrasi Publik, 2026)
The university library is one of the academic support units that plays an important role in supporting the implementation of education, research, and community service, so that the quality of service provided is a determining factor in the level of student satisfaction as service users. This study aims to analyze the quality of service at the Makassar State University Library based on student perceptions using the SERVQUAL approach. The study used a quantitative method with a descriptive approach. The study population was students who used library services, with a sample of 32 respondents selected using an accidental sampling technique. The research instrument was a questionnaire compiled based on five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy, which were analyzed through validity tests, reliability, normality, descriptive statistics, Respondent Achievement Level (TCR), frequency distribution, and data categorization. The results showed that all instrument items were declared valid with a correlation value greater than r table (0.349) and had very high reliability with a Cronbach's Alpha value of 0.913. The overall average value of the service quality variable is 37.03 out of a maximum score of 50 with a TCR of 74.06% which is in the good category. This study concludes that the service quality of Makassar State University Library is in the good category based on student perceptions, so library managers need to continue to improve service quality through facility development, librarian competency enhancement, and information technology-based service optimization.